Correlation of the Content of Surah Al-Waqi'ah with Fadhilah Reciting the Surah - Yuli Eka Lestari; Masruchin Masruchin; Abuzar Alghifari (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2026)
This article examines the correlation between the content of surah al-waqi'ah and the public's belief about the fadhilah of reading it. As surah Makkiyah, surah al-waqi'ah affirms the certainty of the Day of Judgment, the division of human beings into three groups, the Oneness of Allah and the glory of the Qur'an as well as criticism of the attitude of denying His favor. However, in religious practice, this surah is widely believed to have the virtue of bringing sustenance and preventing poverty, which is sourced from hadith even though it is considered dhoif status. This article uses a qualitative method through a literature study with content analysis of classical and contemporary tafsir books in the style of adabi ijtima'i and hadith literature. The results of the study show that there are differences of opinion among hadith scholars regarding the use of dhoif hadith. Some reject it absolutely, some allow it in the context of fadail al-a'mal, and others accept it if there is no authentic hadith. In terms of interpretation, surah al-waqi'ah does not explicitly promise material sustenance, but rather emphasizes the strengthening of faith, eschatological awareness, and encouragement to do righteous deeds. Thus, the correlation between the content of surah al-waqi'ah and its fadhilah lies in the spiritual effects and religious ethos built through regular reading, rather than on the literal promise of materiality. These findings confirm the need for a more proportionate understanding of fadhilah and open up space for further research with an empirical and interdisciplinary approach to examine the impact of this practice on religious and social life.